Kualitas Produk dan Pelayanan Barista bagi Kepuasan Konsumen kedai Hermess Kopi - I Komang Herda Tri Arnawa; I Gde Oka Saputra; Aditya Manggala RS (Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
The objectives of this study are: (1) To determine whether there is a significant effect of product quality on consumer satisfaction at Hermess Kopi Dalung shop in 2021. (2) To determine whether there is a significant influence on the quality of Barista service on consumer satisfaction at Hermess Kopi Dalung shop in 2021. (3) To find out whether there is a significant effect of product quality and barista service quality on consumer satisfaction at the Hermess Kopi Dalung shop in 2021. The method used in this research is descriptive qualitative. Research informants in this study were consumers of the Hermess Kopi Dalung Store in 2021. Sampling was done by interviewing 5 respondents, including students, students and private employees. This method provides direct answers from informants, so that answers can be found from the questions of interviewees given by the researcher. Researchers can conclude that the quality of products from the Hermess Kopi shop is very popular with customers, not only on the coffee menu that is of interest but many also like it from the non-coffee / frappe menu and from the snacks provided. Apart from the quality of the product, it is also greatly influenced by the barista. which is friendly to the customers of the Hermess Kopi Dalung shop which makes customers not feel awkward to shop at the Hermess Kopi Dalung shop. Thus, customers will feel satisfied with the service received by customers, plus the quality of the menu is not less competitive with well-known Coffee Shops. Therefore, product quality and service quality together greatly affect consumer satisfaction at the Hermess Kopi Dalung shop in 2021.